Symbiodinium Functional Diversity in the Coral Siderastrea siderea Is Influenced by Thermal Stress and Reef Environment, but Not Ocean Acidification - Davies, Sarah W.; Ries, Justin B.; Marchetti, Adrian; Castillo, Karl D. (Frontiers in Marine Science, 2018)
Coral bleaching events are increasing in frequency, demanding examination of the physiological and molecular responses of scleractinian corals and their algal symbionts (Symbiodinium sp.) to stressors associated with bleaching. Here we quantify the effects of long-term (95-day) thermal and CO2-acidification stress on photochemical efficiency of in hospite Symbiodinium within the coral Siderastrea siderea, along with corresponding coral color intensity, for corals from two reef zones (forereef, nearshore) on the Mesoamerican Barrier Reef System. We then explore the molecular responses of in hospite Symbiodinium to these stressors via genome-wide gene expression profiling. Elevated temperatures reduced symbiont photochemical efficiencies and were highly correlated with coral color loss. However, photochemical efficiencies of forereef symbionts were more negatively affected by thermal stress than nearshore symbionts, suggesting greater thermal tolerance and/or reduced photodamage in nearshore corals. At control temperatures, CO2-acidification had little effect on symbiont physiology, although forereef symbionts exhibited constitutively higher photochemical efficiencies than nearshore symbionts. Gene expression profiling revealed that S. siderea were dominated by Symbiodinium goreaui (C1), except under thermal stress, which caused shifts to thermotolerant Symbiodinium trenchii (D1a). Comparative transcriptomics of conserved genes across the host and symbiont revealed few differentially expressed S. goreaui genes when compared to S. siderea, highlighting the host’s role in the coral’s response to environmental stress. Although S. goreaui transcriptomes did not vary in response to acidification stress, their gene expression was strongly dependent on reef zone, with forereef S. goreaui exhibiting enrichment of genes associated with photosynthesis. This finding, coupled with constitutively higher forereef S. goreaui photochemical efficiencies, suggests that functional differences in genes associated with primary production exist between reef zones.